PENGARUH PENAMBAHAN DAUN KETAPANG Terminalia catappa TERHADAP PERTUMBUHAN LARVA UDANG VANAME Litopenaeus vannamei PADA SALINITAS 0 PPT - Andre Rachmat Scabra; Muhammad Junaidi; Lalu Aan Okta Rinaldi (Universitas Mataram, 2021)
The main problem faced today is the low level of postlarva vannamei even though various acclimatization methods have developed to low salinity. Efforts are needed to be able to deal with the problem of delayed growth of shrimp maintained at low salinity. One of them is by adding calcium in the cultivation media. Calcium solubility is needed in order to help the process of calcium absorption. This study aim to improve the dissolution rate of calcium with the addition of ketapang leaf for increased production performance and the growth of vaname shrimp larva (Litopenaeus vannamei). This study used completely randomized design (CaCO3) with 5 treatment and 3 replacement. Doses that used in this study were 50 ppm of lime with 0, 0,12, 0,24, 0,36, and 0,48 ppt doses of ketapang leafs. Observational parameters werw absolute growth rate of weight, absolute growth rate of length, survival rate, feed conversion ratio, oxygen consumption rate, calciums level in water and water quality contains temperature, pH, DO, salinity, and ammonia. The results showed that the addition of 0,48 doses of ketapang leaf significantly effected absolute growth rate of length growth, feed conversion ratio, oxygen consumption rate, and calcium level. While the addition of 0,36 doses of ketapang leaf significantly effected survival rate. By the addition of ketapang leaf can improve performance and the growth of vaname shrimp larva.